2014
DOI: 10.1007/s00405-014-3114-3
|View full text |Cite
|
Sign up to set email alerts
|

Ovine ear model for fully endoscopic stapedectomy training

Abstract: Endoscopic surgery of the middle ear is progressively gaining the interest of otologists, as technological advances have overcome some of its main drawbacks. The long learning curve required to master this technique, urges the search for models to practice it. After the validation of sheep's ear as a proper training model for microscopic stapedectomy, our objective is to demonstrate its adequacy for practicing stapes surgery but performed through a fully endoscopic approach. Endoscopic stapedectomy was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Alternative simulators could be considered for future research; for instance, an ovine ear model for fully endoscopic stapedectomy training has been validated. 18 Staff variation across multiple sites is likely to diminish the effect of collection biases. Participants experience an altered angle of approach and view of the middle ear depending on handedness.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative simulators could be considered for future research; for instance, an ovine ear model for fully endoscopic stapedectomy training has been validated. 18 Staff variation across multiple sites is likely to diminish the effect of collection biases. Participants experience an altered angle of approach and view of the middle ear depending on handedness.…”
Section: Discussionmentioning
confidence: 99%
“…However, literature showed that after 10 endoscopic stapes surgeries for an ENT surgeon experienced in microscopic stapes surgery, there was no statistically significant difference in operating time compared to the microscopic stapes surgeries nor in the amount of postoperative adverse events ( 23 ). Also, based on postoperative audiometric results, the endoscopic and the microscopic approach have similar surgical success ( 7 , 9 , 12 , 23 – 26 ). Finally, the use of an endoscope holder can facilitate the two-handed technique of stapes surgery and reduce the fatigue associated with holding the endoscope for extended periods of time ( 10 ).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, a larger proportion of scutum had to be removed using the microscopic approach than the endoscopic approach. No scutum resection reduces the likelihood of, CT manipulation and postoperative dysgeusia ( 12 ). Also, less invasive surgery might lead to less scar formation and complaints during the first weeks of the postoperative course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several authors have explored the feasibility of using different animal and synthetic models as alternatives to cadaveric temporal bone for simulation training in endoscopic ear surgery. The application of the ovine model has been explored in endoscopic procedures such as stapedectomy, 7,11 cochlear implantation, 12 middle-ear implantable devices 8 and endoscopic myringoplasty. 8,13 This is predominantly a result of the remarkable anatomical similarity and tissue quality that it shares with the cadaveric temporal bone.…”
Section: Discussionmentioning
confidence: 99%